2007
DOI: 10.1097/qai.0b013e3180314b46
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotypes and Lamivudine Resistance Mutations in HIV/Hepatitis B Virus-Coinfected Patients

Abstract: Risk transmission group, age, and positive serum HBeAg are the main determinants of distinct HBV virologic variants, including HBV genotypes and LAM-resistant mutants, in HBV/HIV-coinfected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
5
34
1
Order By: Relevance
“…HBV genotypes A and D were most prevalent, and a similar distribution of genotypes was found in a Spanish cohort [41]. HBV genotype A is known to prevail in central and northern Europe and North America, while HBV genotype D is spread worldwide with focuses on the Mediterranean region and the Middle East [42].…”
Section: Prevalence Co-morbidities and Risk Factors Of Replicative Hmentioning
confidence: 73%
“…HBV genotypes A and D were most prevalent, and a similar distribution of genotypes was found in a Spanish cohort [41]. HBV genotype A is known to prevail in central and northern Europe and North America, while HBV genotype D is spread worldwide with focuses on the Mediterranean region and the Middle East [42].…”
Section: Prevalence Co-morbidities and Risk Factors Of Replicative Hmentioning
confidence: 73%
“…This is important since HBV viraemia is associated with the risk of liver-related complications 7 -9 and selection of HBV drug resistance. 34 Chronic HDV was recognized in 14% of HIV-positive patients with chronic hepatitis B in EuroSIDA. This rate is lower than in other series which included more IDUs, 35 as more than half (51%) of HBsAg-positive patients in EuroSIDA were MSM, and IDUs only represented a quarter of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our shorter follow-up time (median 1.72 years, IQR=0.97-2.44) might partially explain the contrast. Notably, although over 99.0% of the individuals in this analysis received 3TC-containing ART, the follow-up of 1.72 years was possibly too short to see the emergence of HBV resistance to 3TC and waning 3TC suppression of HBV; the previous research showed it may take a longer time to develop 3TC resistance (median 40 months) [44]. Similarly, although HCV infection was not being treated, the study period may have been too short to observe the effects of HCV co-infection on HIV outcomes in a younger patient population -approximately 63% of our study population was 30 years of age or younger vs only 31% in that study.…”
Section: Discussionmentioning
confidence: 98%